1996
DOI: 10.1002/art.1780390317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methotrexate on mouse bone cells in culture

Abstract: Objective. We have recently shown that administration of long-term, lowdose methotrexate (MTX) causes severe osteopenia in female rats. This osteopenia is characterized both by decreased osteoblast function without a decrease in osteoblast numbers, and by increased bone resorption that is believed to represent a physiologic remodeling response by osteoclasts. The present study investigates the effects of varying doses of MTX on mouse bone cells in culture.Methods. Cells were obtained by sequential digestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 16 publications
2
13
0
6
Order By: Relevance
“…Osteoclasts, however, were less affected, as the numbers of osteoclasts and the extent of their activity were no different from that observed in untreated rats. 41,42 In vivo data support this latter observation, as markers of bone resorption were suppressed to a much lesser extent than markers of bone formation during treatment of childhood ALL with chemotherapy. Age-related bone loss may be due to an inadequate supply of osteoblast precursor cells and a resultant decline in osteoblast numbers.…”
Section: Chemotherapeutic Agentsmentioning
confidence: 84%
“…Osteoclasts, however, were less affected, as the numbers of osteoclasts and the extent of their activity were no different from that observed in untreated rats. 41,42 In vivo data support this latter observation, as markers of bone resorption were suppressed to a much lesser extent than markers of bone formation during treatment of childhood ALL with chemotherapy. Age-related bone loss may be due to an inadequate supply of osteoblast precursor cells and a resultant decline in osteoblast numbers.…”
Section: Chemotherapeutic Agentsmentioning
confidence: 84%
“…A study reported localized osteopenia and bone pain in two elderly patients affected by RA and treated with MTX [13]: however, given the patients' age, we cannot exclude other pathogenetic mechanisms underlying skeletal alterations. A few studies on small animals, and one study on synovial and bone tissues of patients submitted to surgery for rheumatoid articular lesions, demonstrated the presence of MTX in both trabecular and cortical bone [12,[23][24][25][26][27]. This was linked to the possibility of bone damage, on the basis of inhibition of osteoblastic activity and stimulation of osteoclastic recruitment, resulting in a net increase in bone resorption.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the small growth loss was more likely due to direct effects of MTX on bone remodeling, matrix synthesis, and calcification. 35 In the central diaphysis of the femur, MTX led to an increase in BMD, which also may be due to failure of normal cortical remodeling and reshaping induced by the treatment. These effects did not, under our conditions, lead to a significant change in femoral bone strength.…”
Section: Discussionmentioning
confidence: 99%